Reconstructing Islamic education for the digital era: An integrative framework of tarbiyah, taʿlīm, and taʾdīb - Faelalika Putri Herhan; Khaerudin (Eduvista: Journal of Education and Innovation, 2026)
Digital transformation has created multidimensional challenges for Islamic education, while existing studies tend to examine tarbiyah, ta'lim, and ta'dib separately, leaving the need for an integrated conceptual framework unaddressed. This study aims to reconstruct the paradigm of Islamic education in the digital era by developing an integrative framework of tarbiyah, ta'lim, and ta'dib. A qualitative conceptual approach was employed through library research and content analysis of relevant scholarly literature. The findings propose a conceptual framework integrating spiritual development (tarbiyah), knowledge development and digital literacy (ta'lim), and character formation with digital ethics (ta'dib) to address contemporary challenges in Islamic education. This study contributes by providing a conceptual model that advances the theoretical development of Islamic education and offers a foundation for future empirical research and curriculum innovation in the digital era. Abstrak Transformasi digital menghadirkan tantangan multidimensional bagi pendidikan Islam. Namun, kajian yang ada masih cenderung membahas tarbiyah, ta'lim, dan ta'dib secara terpisah sehingga belum menghasilkan suatu kerangka yang integratif. Penelitian ini bertujuan merekonstruksi paradigma pendidikan Islam di era digital melalui pengembangan kerangka integratif tarbiyah, ta'lim, dan ta'dib. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian konseptual melalui studi kepustakaan dan analisis isi terhadap berbagai literatur yang relevan. Hasil penelitian menghasilkan suatu kerangka konseptual yang mengintegrasikan pembinaan spiritual (tarbiyah), pengembangan pengetahuan dan literasi digital (ta'lim), serta pembentukan karakter dan etika digital (ta'dib) sebagai respons terhadap tantangan pendidikan Islam kontemporer. Kontribusi utama penelitian ini terletak pada pengembangan model konseptual yang memperkuat teori pendidikan Islam sekaligus menjadi landasan bagi penelitian empiris dan inovasi kurikulum di era digital.